Earnings Management and Corporate Governance in UK Listed Companies - Peng, Yunhan (2020)
This paper mainly focuses on exploring the relationship between earnings management and corporate governance and measures the relationship from a quantitative perspective combined with qualitative analysis, which makes the relationship between earnings management and corporate governance clearer and more intuitive. This paper first expounds the definition and theory of corporate governance and earnings management respectively, and then discusses the relationship between corporate governance and earnings management. The sample is constituted with data from 781 UK listed companies, with the appliance of the modified Jones model, earnings management of these companies are quantified. This paper selects the board size, board gender diversity, directors average age and shareholding managers as explanatory variables, firm size and gearing ratio as control variables and earnings management as dependent variable. By applying descriptive statistics, regression analysis and other methods of empirical research on the relationship between corporate governance and earnings management, this paper concludes that board gender diversity, firm size and gearing ratio are significantly correlated with earnings management, of which gearing is positively correlated with earnings management and board gender diversity and firm size are negatively correlated. However, the board size, board average age and share-holding managers do not appear statistically significant effect on earnings management. At last, this paper puts forward some suggestions for future research.